THE INFLUENCE OF THE POLITICIZATION OF BUREAUCRACY AND THE LOCAL HEAD’S AUTHORITY IN APPOINTING AND DISMISSING STRUCTURAL OFFICIALS ON BUREAUCRATIC PROFESSIONALISM IN THE ENVIRONMENT OF THE GORONTALO UTARA GOVERNMENT - Adam, Yullinda; Abdussamad, Zuchri; Hamim, Udin (Public Policy Journal, 2020)
The objective of this research is to analyze the simultaneous influence of the politicization of bureaucracy and the local head’s authority in appointing and dismissing structural officials on bureaucratic professionalism in the Gorontalo Utara government. This research engaged structural officials of all regional apparatus organizations in the environment of the Gorontalo Utara government. Findings demonstrate that politiciziation of bureaucracy had a significant influence on bureaucratic professionalism in the environment of the Gorontalo Utara government; the local head’s authority had a significant influence on bureaucratic professionalism in the environment of the Gorontalo Utara government; and politiciziation of bureaucracy and the authority f local head had a simultaneous significant influence on bureaucratic professionalism in the environment of the Gorontalo Utara government. On the other hand, the local government should confront the attempt of development acceleration and hence called for apparatuses’ professionalism; while it was clear that to manifest professionalism in state civil apparatuses, a merit system should be applied in the management of state civil apparatuses. This research was quantitative, and the research samples were 84 officials working at Gorontalo Utara government. The data analysis technique was double regression analysis. In conclusion, 1) Politiciziation of bureaucracy had a significant positive influence on bureaucratic professionalism in the environment of the Gorontalo Utara government at a coefficient of determination of 66.7%, 2) The local head’s authority had a significant positive influence on bureaucratic professionalism in the environment of the Gorontalo Utara government at a coefficient of determination of 53.9%, and 3) Politiciziation of bureaucracy and the authority of local head had a simultaneous significant positive influence on bureaucratic professionalism in the environment of the Gorontalo Utara government at a coefficient of determination of 71.5%, whereas the rest, which was 28.5%, was influenced by other factors not included in this research model.